The gender monster in Indian cinema: the construction of the transnational other - Raj, Sony Jalarajan; Suresh, Adith K. (My University, 2024)
It is through the discursive definitions of monstrosity that the notion of the monster emerged, often as an idea or metaphor but also as a signifier of physical forms of existence. A monstrous entity that exists in imagination is one that feeds fear and anxiety as emotions that are meant to be enjoyed by their consumption through fictional narratives and literary fantasies. However, the assertion of monstrosity to human bodies or the interpretation of human bodies as monsters creates a different context, a rather serious one, where discussions have to reach the socio-political dimensions of monstrosity. This immediately compels us to analyse the human body in terms of how factors such as gender, sexuality, and race construct identities and their public perception in mainstream society. In India, monsters are a part of popular culture where the literary and visual representations of the non-human are interwoven with the human. The religious imagination of monsters in the form of Gods, demons and mythical creatures is reflected in temple art, sculptures, and paintings, and Indian epics such as Mahabharata and Ramayana have popularised images of the non-human through their epic narrative constructions. The ritual practices and cultural negotiations surrounding the monsters make them more than "metaphors" but "ontological realities that are experienced viscerally, shape human behavior, and leave tangible traces" (Arumugam, 2020, 46). Contrary to Western adaptations, cinematic representations of the Indian monster are modelled on existing folklore narratives and religious tales where the idea of the monster emerges from imaginations and superstitions of the land.
Keywords: monstrosity; pop culture; non-human; India; Indian monster; cinematic representations